Investigation of magnetic field anneal in micro-patterned amorphous ribbon on giant magneto-impedance effect enhancement. Issue 3 (9th October 2018) - Feng, Zhu; Zhi, Shaotao; Guo, Lei; Lei, Chong; Zhou, Yong
Abstract : Purpose: This paper aims to investigate magnetic field anneal in micro-patterned Co-based amorphous ribbon on giant magneto-impedance (GMI) effect enhancement. Design/methodology/approach: The amorphous ribbons were annealed in transverse and longitudinal magnetic field. The influence of different field annealing directions on GMI effect and impedance Z, resistance R and reactance X with a series of line width have been deeply analyzed. Findings: In comparison with GMI sensors microfabricated by unannealed and transversal field annealed ribbons, GMI sensor which was designed and microfabricated by longitudinal field anneal ribbon performs better. The results can be explained by the domain wall motion and domain rotation during annealing process and the geometric structure of Co-based GMI sensor. In addition, shrinking the line width of GMI sensor can promote GMI effect significantly because of the effect of demagnetizing field, and the optimum GMI ratio is 209.7 per cent in longitudinal field annealed GMI sensor with 200 μm line width. Originality/value: In conclusion, annealing in longitudinal magnetic field and decreasing line width can enhance GMI effect in micro-patterned Co-based amorphous ribbon.